Comparison of Incisional Hernia Rates Between General and Gynecological Surgery Procedures - Krista Spear; Daniel L. Davenport; Lance Butler; Margaret Plymale; John Scott Roth (Medicina)
Background and Objectives: Incisional hernias are a common and costly complication of surgery, occurring in up to 20% of midline incisions within 3 years of initial operation. Risk factors for incisional hernia include incision site, fascial closure technique, body mass index (BMI), surgical site infections, and gastrointestinal surgery. Limited studies have compared procedural type as a risk factor for hernia formation. The goal of this study was to examine incisional hernia rates among general surgical and gynecologic procedures. Materials and Methods: We queried our Research Data Warehouse for inpatients who had undergone common open abdominal surgeries between January 2012 and December 2022. Patients’ index operations were identified based upon Current Procedural Terminology (CPT) codes and presence of a postoperative incisional hernia was determined by occurrence of an incisional hernia ICD10 diagnosis code more than 2 weeks postoperatively. The main study outcome was time to incisional hernia diagnosis. Results: A total of 4447 patients were identified. Postoperatively, 241 (5.4%) patients were diagnosed with incisional hernias. Hernia rates at 1, 3 and 5 years were 3% (SE 0.003), 6% (0.004) and 8% (0.005), respectively. Patients undergoing exploratory laparotomy (hazard ratio 3.9, p < 0.001), bowel resection (HR 5.5, p < 0.001), and primary hernia repair (HR 13.0, p < 0.001) were found to have significantly increased risk for incisional hernia development compared to those undergoing hysterectomy, following adjustment for comorbid risks, age, sex, and BMI. Conclusions: Exploratory laparotomy, bowel resection, and primary ventral hernia repair are associated with a higher incidence of incisional hernia relative to gynecologic procedures. This relatively unstudied comparison warrants further investigation.